2015
DOI: 10.1080/1745039x.2014.1002673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size and drying methods of corn on growth performance, digestibility and haematological and immunological characteristics of weaned piglets

Abstract: The objective of this study was to evaluate the effects of particle size and drying methods of corn on growth performance of weaned piglets. Crossbreed weaned piglets (n = 192; Duroc × Landrace × Large White) were assigned to one of four treatments (2 × 2 factorial arrangement). All piglets were fed corn-soybean meal diets and treatments were (1) hot air-dried and coarsely ground corn, (2) hot air-dried and finely ground corn, (3) sun-dried and coarsely ground corn and (4) sun-dried and finely ground corn. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…The brown rice processing was performed following the methodology described by Huang et al (2015). The brown rice processing was performed following the methodology described by Huang et al (2015).…”
Section: Ingredients Sourcing and Particle Size Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…The brown rice processing was performed following the methodology described by Huang et al (2015). The brown rice processing was performed following the methodology described by Huang et al (2015).…”
Section: Ingredients Sourcing and Particle Size Processingmentioning
confidence: 99%
“…Therefore, even if the digestibility of P in organic sources is influenced by brown rice particle size, the digestibility of P shows little difference among diets due to the minor contribution of organic P to TA B L E 5 Effects of brown rice particle size on the apparent total tract digestibility of energy and daily nitrogen and phosphorus balances for nursery pigs* the total absorption of P (Huang et al, 2015). However, differences among feed ingredients may exist and results from this experiment with brown rice should not be extrapolated to other ingredients.…”
Section: Itemmentioning
confidence: 99%
See 1 more Smart Citation
“…Drying technology is the most widely used method in agriculture that can extend the safe storage period of postharvest corn (Khanali, Khakpour Giglou, & Rafiee, ). Traditionally, the majority corn in China are sun‐dried (Huang et al., ). Open‐sun drying has many advantages, including the limited dependence on specialist workers, low capital investment, no fuel demand, minimum maintenance needs, and no pollutant emission to the environment (Aghbashlo, Müller, Mobli, Madadlou, & Rafiee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were observed by Giesemann et al [46], who reported that finishing pigs fed a corn-based diet with a particle size of 641 μm had an increased ATTD of DM, N, and GE compared with pigs fed a diet with a mean particle size of 1,500 μm. Likewise, a reduction in particle size from 900 to 300 μm in corn and sorghum improved the ATTD of GE [36, 47], and an improved ATTD of GE and ether extract was observed as the particle size of corn grain was reduced [48]. The use of pelleting in combination with grinding also may increase ATTD of DM, GE, and N [1].…”
Section: Particle Size Of Feed Ingredientsmentioning
confidence: 99%